2014
DOI: 10.1002/meet.2014.14505101028
|View full text |Cite
|
Sign up to set email alerts
|

Documenting young children's technology use: Observations in the home

Abstract: While there has been much interest in children's use of different technologies, research is often done with school‐age children in their classrooms. This exploratory research study looks at fifteen preschool children (aged three to five) in Queensland, Australia and their use of different technologies in their own homes. This paper examines data from a checklist of technologies available in the home and video recording data of children's interactions with online technologies and other people captured by parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Even though research regarding technology usage by children has been growing in the last decades, especially regarding children over 9 years old (i.e. EU Kids online, undertaken since 2006), studies with children up to 8 years old are still scarce (Brito & Dias, 2018, forthcoming;Given et al, 2014;Mawson, 2013). Also, the research regarding the family's role concerning the usage of technology by children up to 8 years old is limited, being mainly focused on questionnaires that calculate the number of hours they spend per day using technology (Plowman, Stevenson, Stephen, & McPake, 2012;Ponte & Batista, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Even though research regarding technology usage by children has been growing in the last decades, especially regarding children over 9 years old (i.e. EU Kids online, undertaken since 2006), studies with children up to 8 years old are still scarce (Brito & Dias, 2018, forthcoming;Given et al, 2014;Mawson, 2013). Also, the research regarding the family's role concerning the usage of technology by children up to 8 years old is limited, being mainly focused on questionnaires that calculate the number of hours they spend per day using technology (Plowman, Stevenson, Stephen, & McPake, 2012;Ponte & Batista, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The data were also analyzed using an inductive, thematic approach to explore emergent themes related to young children's everyday technology activities in the home. Complete results of these analyses are published elsewhere (e.g., Given et al, 2014). This article reports findings related to the use of the observational method, with a particular focus on the impact of video recording by parents on the types and quality of data gathered.…”
Section: Methodsmentioning
confidence: 99%
“…Handheld digital devices are now common artefacts that are often used both in class and out by primary school aged children and many of their younger counterparts (Danby et al, 2013;Given et al, 2014;Walsh, 2011), with tablets and hand-held devices identified as the most commonly used devices amongst 3-5 year olds (Given et al, 2014). Whether or not children have access to digital technologies in their homes, digital devices can provide a highly stimulating and motivational environment for young students, with applications designed to support children's literacy development demonstrating positive outcomes for users (Flewitt et al, 2014;McManis & Gunnewig, 2012;Reid & Ostashewski, 2011).…”
Section: Digital Technologies In the Classroommentioning
confidence: 99%